2022
DOI: 10.1155/2022/3615619
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COVID-19 Patients Presented with Gastrointestinal and Hepatic Manifestations

Abstract: Background. COVID-19 is rapidly spreading as a global pandemic disease that affects mortality, morbidity, and economic recession worldwide including Myanmar. This study is aimed at investigating the prevalence and temporal nature of gastrointestinal and hepatic manifestations as well as their association with composite clinical endpoints in patients with COVID-19. Method. This was a retrospective hospital-based cohort study conducted on confirmed COVID-19 patients who were admitted to two designated COVID-19 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…(1) GI symptoms in COVID-19 patients in this study may not be related to inflammatory reactions and organ dysfunction [17]; (2) There is a correlation between decreased lymphocyte levels in younger COVID-19 patients as compared to older patients [18]. There is a theory that aging of the immune system can contribute to a "non-reactive" state of the immune system, thereby causing a relative decrease in the number of stable lymphocytes, while in younger populations, the decline in highly active lymphocytes can be influenced by several factors, thus contributing to a relatively higher average difference between younger populations [5]; (3) A meta-analysis study by Huang and Pranata showed that lymphopenia is associated with severe COVID-19.…”
Section: Discussionmentioning
confidence: 80%
“…(1) GI symptoms in COVID-19 patients in this study may not be related to inflammatory reactions and organ dysfunction [17]; (2) There is a correlation between decreased lymphocyte levels in younger COVID-19 patients as compared to older patients [18]. There is a theory that aging of the immune system can contribute to a "non-reactive" state of the immune system, thereby causing a relative decrease in the number of stable lymphocytes, while in younger populations, the decline in highly active lymphocytes can be influenced by several factors, thus contributing to a relatively higher average difference between younger populations [5]; (3) A meta-analysis study by Huang and Pranata showed that lymphopenia is associated with severe COVID-19.…”
Section: Discussionmentioning
confidence: 80%